2023
DOI: 10.1038/s41598-022-26423-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved mineralization of dental enamel by electrokinetic delivery of F− and Ca2+ ions

Abstract: This in vitro study evaluated the effects of the infiltration of F- and Ca2+ ions into human enamel by electrokinetic flow (EKF) on the enamel microhardness and F- content. Sound human enamel ground sections of unerupted third molars were infiltrated with de-ionized water by EKF and with F- ion by EKF respectively. All samples were submitted to two successive transverse acid-etch biopsies (etching times of 30 s and 20 min) to quantify F- ion infiltrated deep into enamel. Remarkably, sound enamel showed a large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Subsequent investigations have demonstrated that following Ca 2+ supplementation, Ca 2+ binds with F − to form insoluble CaF 2 in the gastrointestinal tract or bloodstream. This process reduces the concentration of free F − and facilitates the normal progression of enamel mineralization [25,26]. Additionally, research by Yu et al [27] revealed that, in rats subjected to excessive fluoride intake, both blood and bone fluoride levels increased over time in groups treated with low calcium and normal calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have demonstrated that following Ca 2+ supplementation, Ca 2+ binds with F − to form insoluble CaF 2 in the gastrointestinal tract or bloodstream. This process reduces the concentration of free F − and facilitates the normal progression of enamel mineralization [25,26]. Additionally, research by Yu et al [27] revealed that, in rats subjected to excessive fluoride intake, both blood and bone fluoride levels increased over time in groups treated with low calcium and normal calcium.…”
Section: Discussionmentioning
confidence: 99%